Lack of Increase in Muscle Mitochondrial Protein Synthesis During the Course of Aerobic Exercise and Its Recovery in the Fasting State Irrespective of Obesity - Serrano, Nathan; Tran, Lee; Hoffman, Nyssa; Roust, Lori; De Filippis, Elena A.; Carroll, Chad C.; Patel, Shivam H.; Kras, Katon A.; Buras, Matthew; Katsanos, Christos S. (Frontiers in Physiology, 2021)
Acute aerobic exercise induces skeletal muscle mitochondrial gene expression, which in turn can increase muscle mitochondrial protein synthesis. In this regard, the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), is a master regulator of mitochondrial biogenesis, and thus mitochondrial protein synthesis. However, PGC-1α expression is impaired in muscle of humans with obesity in response to acute aerobic exercise. Therefore, we sought to determine whether muscle mitochondrial protein synthesis is also impaired under the same conditions in humans with obesity. To this end, we measured mitochondrial and mixed-muscle protein synthesis in skeletal muscle of untrained subjects with (body fat: 34.7 ± 2.3 %) and without (body fat: 25.3 ± 3.3 %) obesity in a basal period and during a continuous period that included a 45 mins cycling exercise (performed at an intensity corresponding to 65% of heart rate reserve) and a 3-hour post-exercise recovery. Exercise increased PGC-1α mRNA expression in muscle of subjects without obesity, but not in subjects with obesity. However, muscle mitochondrial protein synthesis did not increase in either subject group. Similarly, mixed-muscle protein synthesis did not increase in either group. Concentrations of plasma amino acids decreased post-exercise in the subjects without obesity, but not in the subjects with obesity. We conclude that neither mitochondrial nor mixed-muscle protein synthesis increase in muscle of humans during the course of a session of aerobic exercise and its recovery period in the fasting state irrespective of obesity.